MENINGKATKAN KEMAMPUAN MENGUCAPKAN NAMA BENDA MELALUI PERMAINAN KARTU BERGAMBAR BAGI ANAK TUNAGRAHITA SEDANG - Elyza - (Jurnal Penelitian Pendidikan Khusus, 2012)
This study aims to improve the ability to say the names of objects by using a picture card game. This study uses the approach Reaserch Single Subject (SSR) with AB designs. Research subject is the child's initials X. Their behavior is the target size "value" in the child's ability to say 10 images that have been provided. Techniques of data collection is done through registration procedures with direct observation. The data obtained were processed in the graph. These results indicate that the ability of the pronunciation of children increased after being given a picture card game. This is evident in the baseline phase (A) is made of observation was six times the value of children's ability to say the object is 10 (30) because the child only mention [es, HP and bag] with intonation, clear and complete. Meanwhile, after a given intervention (B) through a card game as much as 12 times the image is taken, the child's ability to achieve (86.7) because the child is able to name [es, hp, bags, balls, clothes, books, pen, brush] with intonation , clear and complete. While the word [bicycles and shoes] mentioned [bicycles and shoes] to clear it. It can be concluded that the picture card game effectively and can improve their pronunciation of the name of the object. The results of this study is recommended to teachers and researchers in order to subsequently use the picture card game in improving pronunciation Tunagrahita children are